Kajian Faktor yang Mempengaruhi Perubahan Kos Binaan dalam Projek Infrastruktur - Zulaimi, Nurul Najua Natasha; Sarpin, Norliana; Khalid, Zailawati; Masrom, Md. Asrul Nasid; Goh, Kai Chen; Mazlan, Elis Mardzianah (Research in Management of Technology and Business, 2026)
The construction industry, especially large-scale infrastructure projects, often faces issues of construction cost changes due to material price volatility, global economic factors and project management challenges that affect the effectiveness of financial planning. Therefore, the objectives of this study are to identify factors that influence construction cost changes, identify the negative effects of construction cost changes and propose measures to improve the construction cost process for infrastructure projects. This study uses a quantitative method through a questionnaire distributed to G7 contractors in the state of Selangor, with 177 respondents involved out of 346 forms distributed (response rate of 51.2%). The study data was then analyzed using descriptive and reliability statistical methods to ensure the accuracy of the study findings. The study results show that the increase in construction material costs, inflation, shortage of skilled labor and market instability are the main factors contributing to construction cost changes, in addition to affecting project delays, financial pressures and cash flow disruptions. Among the proposed improvement measures that can be implemented are the use of fixed price contracts, periodic monitoring of prices, implementation of continuous training and monitoring and management of labor hours. In conclusion, this study proves that more systematic construction cost management through the use of technology, appropriate contracting strategies and continuous monitoring can help the construction industry control changes in infrastructure project costs and improve the effectiveness of financial planning.